Blocking of injected holes at the charge extracting interface. (14th November 2016) - Govor, L V; Reiter, G; Parisi, J
Abstract: For an organic crystal with four metal electrodes, we have investigated the charge transfer between the injecting electrode 1 and the extracting electrodes 2–4. Each of the measured I − V curves was decomposed into three components, characterizing the injecting and extracting interfaces, and the squaraine (SQ) crystal. We considered a case, where the resistance of the organic crystal was significantly smaller than that of the interfaces. The different values of the contact resistances measured at different electrodes are related to differing values of the barrier height Φ and its width d, which were determined using the Simmons approximation. When the extracting interface has a larger contact resistance compared to that of the SQ crystal and that of the injecting interface, part of the injected holes remains located within the SQ crystal. The voltage V 0, at which the injected hole density begins to exceed the extracted hole density within the SQ crystal, depends on the ratio δ = ( Φ e x × d e x ) / ( Φ i n × d i n ) (indices ex and in describe the extracting and injecting electrodes, respectively). The smaller δ is, the larger is voltage V 0 .